Socialization of the Play with Children Program (Program Beranak) to Mothers of Children with Special Needs - Jiu, Cau Kim; Pratama, Kharisma; Usman, Usman (Society : Jurnal Pengabdian Masyarakat, 2025)
One of the needs of children is play, but some parents are not optimal in utilizing play time with children at home. Although children have special needs such as autism spectrum disorders and intellectual disabilities, the desire to play in children still exists and must be fulfilled by parents. The community service program to play with children, which is called the “Program Beranak”, is one of the programs that aims to bring closer the physical and emotional relationship between mothers and children so that it can increase self-confidence, stimulate cognitive development, social and emotional skills of children with special needs. In addition, playing with children with special needs is a form of therapy so that children can express themselves and train children's concentration. The method of this community service activity was carried out through lectures, small group discussions and simulations. The results of this activity show that there is an increase in the knowledge and skills of mothers who have children with special needs in playing with children at home. Some activities that mothers can do when playing with children at home such as reading fairy tales or storybooks, arranging puzzle toys, painting and coloring. It is expected that mothers can spend time with their children at least 30-45 minutes a day to play and the type of game is adjusted to the age and development of the child.